1999
DOI: 10.1046/j.1365-2885.1999.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of the role of CCK in the opioid modulation of the motility of the gastrointestinal tract in sheep

Abstract: The participation of central cholecystokinin-8 (CCK-8) receptors in the modulatory effect of D-Ala2, N-Me-Phe4, Gly5-ol enkephalin (DAGO), a selective mu-opioid receptor agonist, on the spike burst activity of the gastrointestinal tract (rumen, reticulum, antrum, duodenum, colon and caecum) in sheep was investigated. DAGO was infused intracerebroventricularly (i.c.v.) at doses of 0.1-1 microg/kg body weight (BW). It was shown that DAGO significantly inhibited myoelectrical activity of the wall of the forestoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Further study showed that CCK antagonist L-364,718 could induce the premature phase 3 in ovine duodenum thus confirming indirectly the previous suggestion (Onaga et al, 1997). The opposite effect after central administration of CCK antagonist was obtained by Kania et al (1999). Thus, the aim of this study was to assess the precise effect of CCK-octapeptide (CCK-OP) on the MMC in the entire small intestine of conscious sheep.…”
Section: Introductionsupporting
confidence: 81%
“…Further study showed that CCK antagonist L-364,718 could induce the premature phase 3 in ovine duodenum thus confirming indirectly the previous suggestion (Onaga et al, 1997). The opposite effect after central administration of CCK antagonist was obtained by Kania et al (1999). Thus, the aim of this study was to assess the precise effect of CCK-octapeptide (CCK-OP) on the MMC in the entire small intestine of conscious sheep.…”
Section: Introductionsupporting
confidence: 81%
“…The results obtained were nonsignificant in comparison with the results obtained after the intraduodenal balloon placed and no influencing on the interpretation of the results obtained. Mechanical duodenal distension by balloon 10 cm in length with 40 mL of warm water (DD40) provoked during and after 5 min total inhibition of spiking activity [30,32] or contraction of the rumen and duodenum during 8-12 min (p ≤ 0.01, Figure 2), approximately 85%. These effects, lasting 20 min after DD termination (average 47.3%) were statistically significant (p ≤ 0.05) in comparison to the control values (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of mechanograms and calculations of results were performed similarly as in a case of electromyographic recording [32]. The number of the rumen motor activity was determined by the frequency on mechanograms, with 5 min intervals before and after the DD40.…”
Section: Mechanographymentioning
confidence: 99%
“…However, the morphine can stimulate motilin release, thus its action can be, at least in part, independent of the nervous system (Poitras et al., 1985). In sheep, CCK can interfere with the opioid modulation of the gastrointestinal motility, which suggests that CCK may exert its gastrointestinal motor effects mainly through the neural mechanisms (Kania et al., 1999). In monogastrics it is well known that the nervous system participates in the action of CCK on gastrointestinal motility (Grider, 1994).…”
Section: Discussionmentioning
confidence: 99%